Resolvin D2 Enhances Postischemic Revascularization While Resolving Inflammation. Issue 9 (30th August 2016) - Zhang, Michael J.; Sansbury, Brian E.; Hellmann, Jason; Baker, James F.; Guo, Luping; Parmer, Caitlin M.; Prenner, Joshua C.; Conklin, Daniel J.; Bhatnagar, Aruni; Creager, Mark A.; Spite, Matthew
Abstract : Background: Resolvins are lipid mediators generated by leukocytes during the resolution phase of inflammation. They have been shown to regulate the transition from inflammation to tissue repair; however, it is unknown whether resolvins play a role in tissue revascularization following ischemia. Methods: We used a murine model of hind limb ischemia (HLI), coupled with laser Doppler perfusion imaging, microcomputed tomography, and targeted mass spectrometry, to assess the role of resolvins in revascularization and inflammation resolution. Results: In mice undergoing HLI, we identified resolvin D2 (RvD2) in bone marrow and skeletal muscle by mass spectrometry (n=4–7 per group). We also identified RvD2 in skeletal muscle biopsies from humans with peripheral artery disease. Monocytes were recruited to skeletal muscle during HLI and isolated monocytes produced RvD2 in a lipoxygenase-dependent manner. Exogenous RvD2 enhanced perfusion recovery in HLI and microcomputed tomography of limb vasculature revealed greater volume, with evidence of tortuous arterioles indicative of arteriogenesis (n=6–8 per group). Unlike other treatment strategies for therapeutic revascularization that exacerbate inflammation, RvD2 did not increase vascular permeability, but reduced neutrophil accumulation and the plasma levels of tumor necrosis factor-α and granulocyte macrophage colony-stimulating factor. In mice treated with RvD2, histopathologic analysis of skeletal muscle of ischemic limbs showed more regenerating myocytes with centrally located nuclei. RvD2 enhanced endothelial cell migration in a Rac-dependent manner, via its receptor, GPR18, and Gpr18 -deficient mice had an endogenous defect in perfusion recovery following HLI. Importantly, RvD2 rescued defective revascularization in diabetic mice. ConclusionS: RvD2 stimulates arteriogenic revascularization during HLI, suggesting that resolvins may be a novel class of mediators that both resolve inflammation and promote arteriogenesis.